Does Mind Mapping Matters in Engaging Students’ Creativity and Learning Achievement? - Prayitno, Putra Hilmi; Wibowo, Agus (Classroom Action Research Journal (CARJO), 2019)
This study examines the implementation of Mind-Mapping Model in the classroom and its impacts on creativity and learning achievement of high school students. This paper includes Classroom Action Research which conducted in economics class in a Senior High School in East Java, Indonesia. The data were collected using documentation technique, in-depth interview, and comparing pre-test and post-test results. The findings revealed that the implementation of Mind-Mapping in economics class affects students creativity and learning achievement. There a noticeable change in students’ creativity which is shown by fluency releases creative new ideas easily and quickly, and flexibility in seeing things from another perspective and considering things from the opposite point of view.KeywordsMind Mapping, Students’ Creativity, Learning Achievement